TEMPAT USAHA YANG FLEKSIBEL BAGI GENERASI MUDA - Wilbert Lowira; Himaladin Himaladin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Many young generation face challenges in the world of work due to a lack of understanding of work and adequate adaptation skills. They have difficulty adapting to a new work culture, different rules and procedures, and the demands of co-workers and supervisors. these difficulties also arise in adjusting to longer working hours and higher assignments. Disagreements about directions given by colleagues or superiors often lead to awkwardness at work, which can end in self-reference or dismissal. As a result, their potential is difficult to realize and they have difficulty earning income due to difficulties in adapting to real work life. Therefore we need a platform that can develop the potential of the young generation themselves, as well as take advantage of the potential that exists in them at this time to continue to earn income while they are going through the action phase (looking for a job or have just lost a job). Due to this phenomenon, field surveys, interviews, and collection of documents related to the fresh graduates themselves have been carried out. The purpose of this data collection is to answer the needs in terms of spatial and spatial organization as well as the opportunities that exist today which are intended to make it easier for young generation to achieve their potential development and adapt in the world of work. Keywords: adapt; potential development; work life; young generation Abstrak Banyak generasi muda yang menghadapi tantangan dalam dunia kerja karena kurangnya pemahaman tentang kerja dan keterampilan adaptasi yang memadai. Mereka mengalami kesulitan beradaptasi dengan budaya kerja baru, aturan dan prosedur yang berbeda, serta tuntutan rekan kerja dan supervisor. Kesulitan ini juga muncul dalam menyesuaikan diri dengan jam kerja yang lebih panjang dan tugas yang lebih tinggi. Perbedaan pendapat tentang arahan yang diberikan oleh rekan atau atasan seringkali menyebabkan rasa canggung dalam bekerja, yang dapat berakhir dengan pengunduran diri atau pemecatan. Akibatnya, potensi mereka sulit terwujud dan mereka kesulitan dalam memperoleh penghasilan karena kesulitan dalam beradaptasi dengan kehidupan kerja nyata. Oleh karena itu diperlukan suatu wadah yang bisa mengembangkan potensi diri generasi muda itu sendiri, serta memanfaatkan potensi yang ada pada mereka saat ini untuk tetap mendapatkan penghasilan selagi mereka melalui fase pengangguran (mencari pekerjaan atau baru saja kehilangan pekerjaan). Dikarenakan adanya fenomena tersebut telah dilakukan survei lapangan, wawancara, dan pengumpulan dokumen yang berkaitan dengan fresh graduate itu sendiri. Tujuan pengumpulan data tersebut yakni untuk menjawab mengenai serta peluang yang ada pada zaman sekarang yang diperuntukan untuk memudahkan generasi muda dalam mengembangkan potensi diri dan beradaptasi pada dunia kerja.